An annotated checklist of the spiders (Arachnida: Araneae) of Azerbaijan - Nuruyeva, Tamara; Zamani, Alireza (Zootaxa, 2025)
An updated and annotated checklist of the spiders of Azerbaijan, comprising 775 species in 296 genera and 47 families, is provided. The list includes 44 species currently considered endemic and 44 considered subendemic. A separate list of 62 species excluded from the checklist of Azerbaijani spiders is also provided, including eight species excluded herein. Furthermore, Zelotes egregius Simon, 1914 (Gnaphosidae) is newly recorded from Azerbaijan.